Beneficial use of ultrasound irradiation in synthesis of beta–clinoptilolite composite used in heavy oil upgrading process. Issue 29 (29th May 2019) - Safari, Sahar; Khoshbin, Reza; Karimzadeh, Ramin
Abstract : Beta–clinoptilolite composite synthesized in the presence of ultrasound irradiation exhibited high stability in heavy oil upgrading process while producing equal amount of light fuels and lower amount of coke compared to beta zeolite catalyst. Abstract : A novel beta–clinoptilolite composite was prepared from beta zeolite and alkaline treated clinoptilolite by employing conventional and sonicated mixing procedures. Parent and prepared catalysts were characterized by XRD, FE-SEM, N2 adsorption–desorption and NH3 -TPD analyses. Prepared composite of beta zeolite and treated clinoptilolite exhibited improved structural properties especially upon sonicated mixing procedure. Employing ultrasound irradiation notably improved beta distribution in the composite and increased mesoporous volume and specific surface area from 0.245 cm 3 g −1 and 171.3 m 2 g −1 in conventionally mixed composite to 0.353 cm 3 g −1 and 232.9 m 2 g −1 in sonicated sample. Catalytic performance of prepared composite was evaluated in heavy oil upgrading process in a continuous fixed bed apparatus. Liquid product was specified by conducting SIMDIS-GC and GC/MS analyses. Spent catalysts were characterized by TGA, FTIR and XRD. Beta–clinoptilolite composite containing only 30 wt% of beta zeolite, exhibited similar performance to beta zeolite catalyst by resulting 75.3% viscosity reduction while producing lower amount of coke. Amount of light hydrocarbons produced over beta–clinoptilolite composite was 33.51 wt% while beta zeolite catalyst produced 35.58 wt% light hydrocarbons in upgrading process. Ultrasound irradiated composite showed more stable structure in catalytic cracking procedure compared to conventionally mixed composite. After 5 h time on stream, relative crystallinity of clinoptilolite phase in the conventionally mixed composite was reduced by 34.5% while sonicated sample remarkably preserved its structure during the reaction and only 1% reduction occurred for this sample.